(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Endometriosis is a common gynaecological condition affecting a significant proportion of reproductive-age individuals. Despite its prevalence, diagnostic delays remain widespread. This article discusses the key diagnostic challenges and highlights current advances in medical and surgical management of the disease.